Green banking illusion? The influence of “Eco-Conscious” bank shareholders on credit allocation - Böhm, Adrian; Eufinger, Christian; Kadach, Igor; Sakasai, Yuki (Journal of Corporate Finance, 2025)
Can voluntary market-based initiatives effectively promote greener credit allocation? Our paper addresses this question by assessing the role of self-declared environmentally conscious bank shareholders, specifically those endorsing the UN Principles for Responsible Investment, in shaping the sustainability of bank loan portfolios. For our analysis, we utilize a comprehensive dataset that includes information on syndicated loans, firm-level emissions, and both bank and firm ownership and financial data. Controlling for loan demand, at the bank–firm level, we find no evidence of an association between a higher ownership stake by eco-conscious bank shareholders and shifts in banks’ loan allocation strategies between firms with low and high emissions. At the firm-level, we find that lending relationships with banks characterized by greater eco-conscious ownership are not associated with significantly improved environmental performance among borrower firms. Our analysis reveals that banks are treated differently by investors compared to non-financial firms, likely due to regulatory requirements and their unique governance structures, which might explain the observed lack of influence of eco-conscious bank shareholders. Our findings thus indicate the potential limitations of relying on self-declared eco-conscious bank shareholders to guide banks toward environmentally sustainable credit allocation.